2021
DOI: 10.1016/j.ultsonch.2021.105768
|View full text |Cite
|
Sign up to set email alerts
|

Energetic study of ultrasonic wettability enhancement

Abstract: Highlights Ultrasonic vibration reduces the contact angle through the amplitude modulation. Contact angle hysteresis and capillary waves induce a non-returning mechanism. A thermodynamical model has been developed and validated. Ultrasound enhanced wetting is energetically very efficient and non-polluting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…On the other hand, it is well known that ultrasonic vibration improves wettability of solids. This is supported, for example, by Sarasua et al [44] who reported that ultrasonic vibrations result in reduction of the contact angle with no return. Therefore, we believe that the profile of aluminum melt surface near the sonotrode is not too different from what we observed in the water model experiments.…”
Section: Discussionsupporting
confidence: 65%
“…On the other hand, it is well known that ultrasonic vibration improves wettability of solids. This is supported, for example, by Sarasua et al [44] who reported that ultrasonic vibrations result in reduction of the contact angle with no return. Therefore, we believe that the profile of aluminum melt surface near the sonotrode is not too different from what we observed in the water model experiments.…”
Section: Discussionsupporting
confidence: 65%
“…In a previous paper the same authors [19,22] demonstrate that the combination of ultrasonic vibration with contact angle hysteresis results in a non-return mechanism that expands the droplet (Figure 1) until half the acoustic energy introduced is consumed. The non-return mechanism is therefore related to the advancing, receding and critical sliding angles.…”
Section: Introductionmentioning
confidence: 84%
“…It has been studied by many authors, including Lauterborn [13][14][15] and Mason [16], who conclude that the size, number and distribution of bubbles depend mainly on the ultrasonic parameters (amplitude and frequency) and the liquid itself (volume, surface tension, density and viscosity). However, another physical phenomenon has been described by several authors [17][18][19][20]: the contact angle is changed when liquids are exposed to low and high frequency vibration. Manor et al [21] describe a vibration driving force F [N] at megasonic frequency.…”
Section: Introductionmentioning
confidence: 99%
“…In this Review, we are not focusing on the surface fabrication processes to modify the wettability of surfaces; instead, we critically discuss the behavior of liquids when they come in contact with such surfaces and the implications of these interactions in various applications. Furthermore, active methods such as those using electric fields, , acoustic waves, , and magnetic fields, leverage external forces and stimuli to manipulate the behavior of liquids on solid surfaces. The present Review does not focus on such external control of surface wetting.…”
Section: Introductionmentioning
confidence: 99%